A "Look Back" and "Look Forward": The Compensation of Business Leaders in the 21st Century. (September 2013) - Graham, Michael Dennis
Michael Graham discusses changes in the executive compensation landscape over the past decade and makes the case that since the mid-2000s, the world has changed dramatically but executive compensation structures and approaches have not necessarily kept pace. Graham addresses the changes relating to business environment, regulations, stakeholders, vision, strategy, organizational capabilities and program components. He discusses how executive compensation approaches could be better structured to address relevant changes in these areas.